Simulation of Dynamic Thermal Behaviour for Housing in Warm Climate: The Case of Thermal Mass in Lightweight Envelopes - Tonelli, Chiara; Montella, Ilaria (Journal of Technology Innovations in Renewable Energy, 2018)
Comparison between simulation results and measured performances is usually an open scientific problem, crucial to achieving the goal of NZEB performance. This paper addresses this issue in relation to residential buildings, using as a case study "RhOME for denCity", the housing prototype developed by Roma TRE University and winner of Solar Decathlon Europe 2014. In a Mediterranean climate, the use of the mass combined with natural cross ventilation to control the indoor microclimate can be very effective in reducing HVAC use. Therefore, a "massive layer" was introduced in the inner surface of the envelope to not only contribute to the envelope transmittance value and the shifting phase of the thermal waves, but also as a thermal shock absorber to adjust the internal temperature, in both summer and winter. This experimental envelope was tested over two weeks during the competition in Versailles. Although prototype thermal behaviour was monitored only during the competition, and not over an extended period, initial results provide information on how to size the thermal mass contribution for indoor comfort. In-depth simulation through TRNSYS was run prior to the construction phase. This paper presents the comparison between monitored performance and simulations in order to measure the amount of mass needed to obtain a numerical improvement in indoor comfort performance.